On Qualitative Properties of \(L_Θ\)-Solutions for Coupled Systems of Hadamard-Type Fractional Integral Equations in Banach Spaces (European Journal of Pure and Applied Mathematics, 2025)
In this manuscript, the measure of noncompactness ($\mathbf{\mathcal{MNC}}$), Darbo and Banach contraction fixed point theorems ($\mathbf{\mathcal{FPT}}$), as well as fractional calculus, are used to carry out the analysis of the solvability of a general but abstract coupled system of quadratic Hadamard-fractional integral equations in Orlicz spaces $L_Θ$. Several qualitative properties of the solution to the studied coupled system are established, such as the existence, monotonicity, and uniqueness, in addition to continuous dependence on the data. We conclude with some examples that illustrate our hypothesis.